The Poetry of Postmodernity - Brown, D. author. aut Link
X, 146 p.
Keywords: The Poetry of Postmodernity reappraises key Anglo/American poets of the last fifty years in the light of debates about the postmodern situation. It offers fresh critical insights into how their literary contribution gives cogent expression to both the socio-cultural possibilities and the global problems of our recent past, our apparent present and our probable future. The poets considered are late Auden, Ginsberg, Plath, Berryman, Hughes, Hill, Ashbery and late R.S. Thomas.